Bacterial community assembly driven by temporal succession rather than spatial heterogeneity in Lake Bosten: a large lake suffering from eutrophication and salinization - Liu, Hao; Dai, Jiangyu; Fan, Ziwu; Yang, Bei; Wang, Hang; Hu, Yang; Shao, Keqiang; Gao, Guang; Tang, Xiangming (Frontiers in Microbiology, 2023)
Oligosaline lakes in arid and semi-arid regions play a crucial role in providing essential water resources for local populations. However, limited research exists on the impact of the environment on bacterial community structure in these lakes, co-occurrence patterns and the mechanisms governing bacterial community assembly. This study aims to address this knowledge gap by examining samples collected from five areas of Lake Bosten over four seasons. Using the 16S rRNA gene sequencing method, we identified a total of 510 to 1,005 operational taxonomic units (OTUs) belonging to 37 phyla and 359 genera in Lake Bosten. The major bacterial phyla were Proteobacteria (46.5%), Actinobacteria (25.9%), Bacteroidetes (13.2%), and Cyanobacteria (5.7%), while the major genera were hgcI_clade (12.9%), Limnohabitans (6.2%), and Polynucleobacter (4.7%). Water temperature emerged as the primary driver of these community structure variations on global level. However, when considering only seasonal variations, pH and nitrate were identified as key factors influencing bacterial community structures. Summer differed from other seasons in aspects of seasonal symbiotic patterns of bacterial communities, community assembly and function are different from other seasons. There were notable variations in bacterial community structures between winter and summer. Deterministic processes dominated community assembly, but there was an increase in the proportion of stochastic processes during summer. In summer, the functions related to photosynthesis, nitrogen fixation, and decomposition of organic matter showed higher abundance. Our findings shed light on the response of bacterial communities to environmental changes and the underlying mechanisms of community assembly in oligosaline lakes in arid regions.